Application of plant extracts to improve the shelf-life, nutritional and health-related properties of ready-to-eat meat products. (November 2018) - Nikmaram, Nooshin; Budaraju, Sravanthi; Barba, Francisco J.; Lorenzo, Jose M.; Cox, Ryan B.; Mallikarjunan, Kumar; Roohinejad, Shahin
Abstract: Plant extracts are increasingly becoming important additives in food industry due to their antimicrobial and antioxidant abilities that delay the development of off-flavors and improve the color stability in ready-to-eat (RTE) meat products. Due to their natural origin, they are excellent candidates to replace synthetic molecules, which are generally considered to have toxicological and carcinogenic effects. The efficient extraction of these antioxidant molecules from their natural sources, along with the determination of their activity in the commercialized products, have been a great challenge for researchers and food chain contributors. The objective of this review is to highlight the application of plant extracts to improve the shelf-life, nutritional and health-related properties of RTE meat products. The sensory effects of these extracts on RTE meat products as well as the possible synergistic effects of a combination of extracts are discussed.